Relevance of the Myeloid Differentiation Factor 88 (MyD88) on RANKL, OPG, and Nod Expressions Induced by TLR and IL-1R Signaling in Bone Marrow Stromal Cells - Leite, Fábio Renato Manzolli [UNESP]; Aquino, Sabrina Garcia de [UNESP]; Guimarães, Morgana Rodrigues[UNESP]; Cirelli, Joni Augusto [UNESP]; Zamboni, Dario S.; Silva, João S.; Rossa Júnior, Carlos [UNESP] (Springer Nature, 2014)
The myeloid differentiation factor 88 (MyD88) plays a pivotal role in Toll-like receptor (TLR)- and interleukin-1 receptor (IL-1R)-induced osteoclastogenesis. We examined the role of MyD88 on p38 mitogen-activated protein kinase (MAPK) and nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB) activation and nucleotide-binding oligomerization domain (Nod) induction by lipopolysaccharide (LPS) and IL-1 beta, and their effect on receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG) production in bone marrow stromal cell (BMSC). RANKL, Nod1, Nod2, NF-κB, and p38 protein levels were determined by Western blot. Nod2 was stimulated with muramyl dipeptide (MDP) prior to TLR4 stimulation with LPS. MyD88 deficiency markedly inhibited RANKL expression after LPS stimulation and increased OPG messenger RNA (mRNA) production. Also, MyD88 was necessary for NF-κB and p38 MAPK activation. MDP alone did not induce RANKL and OPG expressions; however, when combined with LPS, their expressions were significantly increased (p < 0.05). Our results support that MyD88 signaling has a pivotal role in osteoclastogenesis thought NF-κB and p38 activation. Nod2 and especially Nod1 levels were influenced by MyD88.
Keywords: Lipopolysaccharide; Signaling pathway; Mitogen-activated protein kinases; Nuclear factor; Kappa-light-chain-enhancer of activated B cells; Receptor activator for nuclear factor k B ligand; Osteoprotegerin